The Spread of Modern Western Medicine in China: The Case of the Medical School of Zhenduan University, Intertwined with Its Dual Identities as French and Catholic - REN Yi, (Journal of Research for Christianity in China (JRCC), 2025)
The Medical College of Aurora University integrated the French elite education model into the cultivation of specialized talent in modern China, continuing the Jesuits' rigorous educational tradition. Though slightly less prominent than Protestant institutions, Aurora University achieved maximum success by seamlessly blending French higher education with China's national context. Simultaneously, through indirect and pervasive religious education, the flourishing of Aurora Medical College shattered Protestant dominance in scientific fields, demonstrating that the Catholic Church served not only impoverished peasants but also the intellectual elite. Characterized by its Catholic and Jesuit identity, Aurora University's distinctive educational approach enriched the diversity of modern Chinese higher education while reflecting Europe's non-colonial, soft expansion into East Asia.